2004
DOI: 10.1002/dev.20036
|View full text |Cite
|
Sign up to set email alerts
|

Stability of respiratory sinus arrhythmia in children and young adolescents: A longitudinal examination

Abstract: The stability of children's baseline respiratory sinus arrhythmia (RSA) and RSA regulation were examined longitudinally, with a 2-year lag between each of two waves of data collection. Associations between baseline RSA and RSA regulation also were examined in this study. During two laboratory sessions, 2 years apart, children were exposed to two stressors: exposure to an audiotaped conflict between two adults and a problem-solving task in which the child had to trace a star while looking into a mirror. Measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
179
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(192 citation statements)
references
References 36 publications
12
179
1
Order By: Relevance
“…29 weeks), as opposed to preschool (Morales et al., 2015) and school‐aged children (Eisenberg et al., 1995; Hinnant & El‐Sheikh, 2013) in previous studies. Baseline vagal tone has been shown to be moderately stable from preschool or middle childhood onwards (Calkins & Keane, 2004; El‐Sheikh, 2005) but less so in the first years of life (Bornstein & Suess, 2000), which might also have an impact in the results.…”
Section: Discussionmentioning
confidence: 99%
“…29 weeks), as opposed to preschool (Morales et al., 2015) and school‐aged children (Eisenberg et al., 1995; Hinnant & El‐Sheikh, 2013) in previous studies. Baseline vagal tone has been shown to be moderately stable from preschool or middle childhood onwards (Calkins & Keane, 2004; El‐Sheikh, 2005) but less so in the first years of life (Bornstein & Suess, 2000), which might also have an impact in the results.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, both sympathetic and parasympathetic reactivity have been associated with lower competence and lower mental and physical health in the context of high adversity, but higher competence and health in the context of low adversity. For example, high SCL reactivity to emotional and cognitive tasks was associated with high or increasing levels of internalizing symptoms, externalizing symptoms, and social and cognitive problems, but only in children who were exposed to high levels of paternal depression [53] or marital conflict [54,55] . Similarly, a recent study of kindergartners demonstrated that high RSA reactivity was associated with higher levels of externalizing problems and lower levels of prosocial behavior, school engagement, and academic competence in the context of high family adversity.…”
Section: Physiological Sensitivitymentioning
confidence: 99%
“…Such individuals thus show either the least or most adaptive outcomes within the population, depending on the character of the proximal social contexts in which they are reared. Studies demonstrating this greater susceptibility of neurobiologically responsive children to both positive and negative aspects of their environments have implicated a wide variety of stressors and adversities, including paternal depression (67), marital conflict (68,69), parental psychopathology (70), and overall family distress (71); of positive environmental features, including parental warmth (72) and supportive interventions (73); and of defining biological parameters, including physiological reactivity (e.g., 74, 75), differences in brain circuitry (76), and gene polymorphisms (77,78). Most importantly, highly susceptible children show bidirectional effects on outcomes in contrasting low-and high-stress settings, not simply an attenuation of negative effects in low-stress circumstances.…”
mentioning
confidence: 99%